Country risks analysis for the development of green hydrogen and synthetic fuel sectors in the MENA region - Terrapon-Pfaff, Julia; Ersoy, Sibel Raquel; Prantner, Magdolna; Viebahn, Peter (Frontiers in Energy Research, 2024)
Hydrogen plays a pivotal role in global efforts to decarbonize energy and industrial sectors. The European Union, particularly Germany, anticipate a significant reliance on hydrogen imports in the medium to long term, identifying the Middle East and North Africa (MENA) region as a key potential producer and exporter of green hydrogen and its downstream products. Yet, investment risks pose significant challenges to advancing the region’s green hydrogen and synthetic fuel industries. However, systematic comparative risk analyses for these sectors across MENA countries remain limited. This study addresses the research gap by conducting a comparative risk assessment for renewable energy and green hydrogen and synthetic fuel development in 17 MENA countries. A comprehensive framework evaluating macro and micro risks was applied, along with two contrasting risk scenarios to explore future developments under different risk conditions. The findings reveal that while MENA countries hold promise, most face at least moderate risks, underscoring the complexity of fostering these industries regionally.